Basic requirements to establish a neuromuscular laboratory - Bevinahalli N Nandeesh; Gayathri Narayanappa; T C Yasha (Wolters Kluwer Medknow Publications, 2022)
Histopathological analysis of muscle biopsy is a prerequisite in the evaluation of neuromuscular disorders, particularly inflammatory myopathies, metabolic myopathies, congenital myopathies, muscular dystrophies and differentiating myopathies and neurogenic disorders with overlapping clinically features. It not only provides useful information that helps in the diagnosis but also treatment and management. Fundamental skills and basic knowledge regarding handling, processing and analyzing a muscle biopsy are required in any specialized or a general pathology lab supporting neuromuscular clinical services. Care during transport of the muscle biopsy, sample receipt in the laboratory and grossing is very important. Standard operating procedure should be followed for the preanalytical steps (freezing and cryomicrotomy), routine and special staining (enzyme and non enzymatic) and immunohistochemistry. A well organized neuromuscular laboratory with good quality management system is necessary for the practice of myopathology. This article gives an overview of establishing such a laboratory.